Synthesis of a smart bisbenzoxazine with combined advantages of bismaleimide and benzoxazine resins and its unexpected formation of very high performance cross-linked polybenzoxazole. (3rd May 2021) - Zhang, Kan; Hao, Boran; Ishida, Hatsuo
Abstract: We report a bisbenzoxazine thermosetting system, o HPMI-ddm, which shows combined advantages of both bismaleimide and benzoxazine resins. The chemical structure of o HPMI-ddm has been identified by FT-IR and NMR spectroscopies, and its polymerization processes have been investigated using differential scanning calorimetry (DSC) and in situ FT-IR. The resulting polybenzoxazine derived from this thermosetting system exhibits significantly higher thermal stability than thermosets polymerized from the commercialized 4, 4′-diaminodiphenylmethane based bisbenzoxazine (PH-ddm) and bismaleimide (DDM-BMI). This newly obtained benzoxazine also shows a unique structural thermal rearrangement in comparison to the cross-linked polybenzoxazole in a similar manner as other reported smart ortho- benzoxazines, although it has no obvious hydrogen bond forming group and cannot form 5- or 6-membered intramolecular interaction. Such conversion from polybenzoxazine to polybenzoxazole has been confirmed by both in situ FT-IR and solid state 13 C NMR. Furthermore, the finally obtained cross-linked polybenzoxazole possesses outstanding properties of high thermal stability, excellent flame retardancy and low dielectric constant, indicating great potential for high performance material applications. Graphical abstract: Image 1